Environmental implications of Chitosan nanostructures. - Rakshita Chaudhary; Prerna Banerjee; Nisha Gaur; Surabhi Bajpai; Kapil Joshi (International Journal of Antibiotics, 2024)
Chitosan (CS), as a biopolymer, has unrivalled chemical and mechanical modification capabilities to develop novel characteristics, functions, and applications, particularly in the manufacture of cutting-edge membrane adsorbents. Membrane adsorbents utilizing carbon starch (CS) have emerged as a viable and efficient engineering instrument for eliminating diverse pollutants from aquatic settings, including heavy metals and dyes. To date, much study has been directed towards improving the adsorptive characteristics, permeability, physicochemical stability, and sustainability of CS-based membranes through the use of various types of nanoparticles (NPs). Additionally, nanoparticles (NPs) can be applied to personalise the appearance and performance of nano-structured and nano-fibrous membranes made from chitosan (CS). This chapter focuses on the utilisation of various types of nanoparticles in CS-based membrane adsorbents, comprising four major groups of metal-based, non-carbon mineral, carbonic (carbon-based), and Metal Organic Frameworks (MOFs). The review and discussion have been broadened to cover manufacturing methods and the effects of adding nanoparticles (NPs) on the chemistry, morphology, adsorption kinetics, and removal effectiveness of membranes made of chitosan (CS). This review might help researchers choose appropriate NP modifiers and preparation procedures for synthesising Nano composite CS membrane adsorbents for varied applications. Advances in chitosan modification, primarily with nanomaterials such as multi-walled carbon nanotubes and nanoparticles (TiO2, Ag, S, and ZnO), and their application for environmental remediation
Keywords: Chitosan; Nanoparticles; nano-fibrous membranes and Metal Organic Frameworks (MOFs); nano-structured membranes